Financial Performance Analysis at CV Hasna Laundry RSU PKU Muhammadiyah Delanggu 2019-2023 - Pratiwi, A. Adelia; Laba, Abd Rakhman; Rahim, Fauzi R. (STIE Amkop Makassar, 2024)
Financial Performance Analysis at CV Hasna Laundry RS PKU Muhammadiyah Delanggu 2019-2023 (Guided by Mr Abd. Rakhman Laba, and Mr. Fauzi R. Rahim). This research aims to analyz the financial performance of CV Hasna Laundry at RS PKU Muhammadiyah Delanggu from 2019 to 2023. Operating in the growing laundry service industry, CV Hasna Laundry primarily caters to industrial clients, including hospitals, where maintaining cleanliness and hygiene is crucial. The study assess the company's financial performance using various financial ratios, such as liquidity, solvency, activity, and profitability ratios, the study provides a comprehensive understanding of its financial condition. The analysis reveals a general trend of increasing laundry service demand, with notable fluctuations due to seasonal factors and the pandemic's impact. The findings suggest that CV Hasna Laundry experienced significant growth in 2020 and 2021, driven by heightened hygiene awareness and increased laundry needs during the pandemic. However, the growth rate stabilized post-pandemic, emphasizing the need for strategic planning to sustain business operations and enhance service quality.